'Maqasid al-shariah' in Islamic banks before value- based intermediation implementation / Sharifah Faigah Syed Alwi … [et al.] - Syed Alwi, Sharifah Faigah; Abd Halim, Fateha; Tengku Ahmad Mazlin, Tengku Dewi Ahdiyaty; Abdul Kadir, Aizurra Haidah; Saiful Fikri, Aula Ahmad Hafidh (UiTM Press, 2021)
Bank Negara Malaysia (BNM) had introduced Value-Based Intermediation (VBI) initiatives to help Islamic banks implement a structuralized form of maqasid al-shariah (objectives of shariah (Islamic law)) in their banking operations. Thus, questions were raised by the public on whether or not Islamic banking institutions in Malaysia had been achieving maqasid alshariah in their banking operations prior to VBI. This paper aims to discuss the real concept of maqasid al-shariah that should be realised in Islamic banks and investigate whether Islamic banks had truly been achieving maqasid al-shariah in their banking operations before the introduction of VBI. Library research is conducted to obtain information on maqasid al-shariah and the qualitative methodology is adopted to gain information from three bankers representing three Islamic banks in Malaysia via semi structured interviews. The researchers found that the fundamental concept of maqasid al-shariah in Islamic banks includes the protection of religion, life, intellect, progeny and wealth in human life through the products and services offered by the banks. The Islamic banks were found to have developed their products and services to achieve maqasid al-shariah even before VBI was introduced by BNM. However, with VBI, a proper framework in achieving maqasid al-shariah has been developed.